Um comentário sobre o legado de Protágoras à filosofia ético-política de Aristóteles - Marisa Lopes (Araucaria)
Protagoras and Aristotle’s conceptions of virtue are without doubt different. The former conceives it as the exercise of certain moral qualities that are indispensable to the attainment or maintenance of what is useful to oneself and to those who dedicate themselves to the affairs of the city. The latter conceives it as a strong and immutable state of character, which is the condition for the realization of the individual’s and of the city’s Eudaimonia. It would seem, however, that Protagoras and Aristotle converge on this point: the subsistence of a city does not depend upon a ruler who holds the science of ruling well with which he rules, but rather on well educated and excellent rulers and citizens, which is the condition for good political exercise. My aim here is to indicate the affinity between the political conceptions of Protagoras and Aristotle concerning the end of civic education as a guarantee of justice in the city.